Estimating the waste heat recovery in the European Union Industry - Bianchi, Giuseppe; Panayiotou, Gregoris; Aresti, Lazaros; Kalogirou, Soteris A.; Florides, Georgios A.; Tsamos, Kostantinos; Tassou, Savvas A.; Christodoulides, Paul (My University, 2019)
Industrial processes are currently responsible for nearly 26% of European primary energy consumptions and are characterized by a multitude of energy losses. Among them, the ones that occur as heat streams rejected to the environment in the form of exhausts or effluents take place at different temperature levels. The reduction or recovery of such types of energy flows will undoubtedly contribute to the achievement of improved environmental performance as well as to reduce the overall manufacturing costs of goods. In this scenario, the current work aims at outlining the prospects of potential for industrial waste heat recovery in the European Union (EU) upon identification and quantification of primary energy consumptions among the major industrial sectors and their related waste streams and temperature levels. The paper introduces a new approach toward estimating the waste heat recovery in the European Union industry, using the Carnot efficiency in relation to the temperature levels of the processes involved. The assessment is carried out using EU statistical energy databases. The overall EU thermal energy waste is quantified at 920 TWh theoretical potential and 279 TWh Carnot potential.
Keywords: Carnot potential; Energy recovery; Energy statistics; Heat to power conversion; Waste heat recovery; WHR Europe; WHR potential estimation